PEMERINTAHAN ALI BIN ABI THALIB DAN PERMULAAN KONFLIK UMAT ISLAM - JUNAIDIN, JUNAIDIN (STIT Sunan Giri Bima, 2020)
This article intends to review how the history of the government of Ali bin Abhi Talib's friends who later got a rebellion from the community at that time. This is inseparable from the aftermath of the policies taken by Ali ibn Abhi Talib who was considered so rash because he dared to bring down officials who were appointed by Uthman ibn Affan's friends before his supporters officially pledged Ali as Khalifah. Moreover, efforts to demand the death of Uthman by his family are like Aisha, Talha, and Zubair, which was then used by Muawiyah ibn Abu Suffyan as an opportunity to bring down Ali ibn Abhi Talib. So the polemic gave birth to the Jamal war, the Siffin war, and the legendary events of Tahkim. Amr's cunning diplomatic power then lowered Ali as Caliph and raised Muawiyah as the official Caliph. The emergence of Khawarij as a rebel who intends to kill Ali, Muawiyah and Amr increasingly adds suspicion to the Muawiyah camp. Considering that only Ali was killed by the Khawarij, while Amr and Muawiyah survived. Ali's death also started a new chapter of the emergence of the Umayyad dynasty.